Análisis de Fourier sobre ZN y conjuntos Bh (2010)
A set A of positive integers is called a Bh set, if all sums ofh elements of A are different. In this paper we use basic properties ofFourier analysis on ZN and follow the style of Ben Green [4] to concludewith a different method, the upper bounds obtained by Jia [6], Chen [2] andGraham [5] with respect to the maximum cardinal that can have a Bh setcontained in the first N positive integers.